Nida Sinnokrot: Rawabi 2014/ Rawabi, 2014 (3fOGA SfbQW(B: (3QhGHj (B2014 s - Sinnokrot, Nida (Darat al Funun, The Khalid Shoman Foundation, 2014)
Program schedule literature, May-June 2014, Tuesdays at the Darat.
English; Arabic
Keywords: NX798-820 Arts centers and facilities; Palestine